Long-Term Storage of Plant-Pathogenic Bacteria in Sterile Distilled Water - Iacobellis, Nicola S. (1986)
This study was made to determine the effectiveness of the preservation of plant-pathogenic bacteria in sterile distilled water. After 20 or 24 years of storage in distilled water, a very high percentage (90 to 92%) of the isolates of Agrobacterium tumefaciens and Pseudomonas spp. were still alive. Moreover, 12 of 13 viable (after 24 years) isolates of P. syringae subsp. syringae maintained their ability to produce syringomycin and were pathogenic to bean seedlings. The water-stored cells of two isolates of P. syringae subsp. syringae, when observed by electron microscopy, were smaller than cells of 24-h-old subcultures of bacterial cells grown in nutrient broth; the water-stored cells appeared plasmolysed with an electron-dense cytoplasm and thickened cell wall.